English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
2

So far I have this

x-y=10
2x+3y=5

y=10+x

2x+30=15
-30 -30

2x=-15/2= -7

x=-7

Is that right? How do I solve for y?

2007-09-15 12:55:57 · 10 answers · asked by ? 4 in Science & Mathematics Mathematics

This is the substitution method.

2007-09-15 12:57:59 · update #1

Please explain how you got the answer.

2007-09-15 14:44:33 · update #2

step by step directions

2007-09-15 14:49:52 · update #3

10 answers

i dont think its right
x-y=10 > let this be our equation 1
2x+3y=5 > let this be our equation 2

From Eq 1

x=10+y this be Eq 3

Substitute Eq 3 into Eq 2
2(10+y) +3y=5
20+2y+3y=5
20+5y=5
5y=5-20
5y=-15
y=-3

put the value of y in eq 3
and we will have
x=10+y
x=10+(-3)
x=10-3
x=7

(7,-3) is the solution

2007-09-15 13:07:12 · answer #1 · answered by Arsalan 1 · 2 0

It is not right.

if x -y = 10, then subtracting x from both sides gives
-y = 10 - x
Multiplying each side by -1 givs
y = -10 + x or y = x - 10
substituting into the second equation gives
2x + 3(x-10) = 5
or 2x + 3x -30 = 5
or 5x -30 = 5
or 5x=5 + 30
or 5x = 35
so x = 35/5 = 7

You are a minus sign off. Not bad.

Now that x = 7, substitute it into either equation
x - y = 10
7 - y = 10
y = x -10
y = 7 - 10 = -3

2007-09-15 13:07:55 · answer #2 · answered by drslowpoke 5 · 0 0

x-y=10
2x+3y=5

-y=10 - x
y = -10 + x

2x + 3( -10 + x) = 5
2x - 30 + 3x = 5
5x = 35
x = 7

Solve for y with the equation above: y = -10 + x
y = -10 + x = -10 + 7 = -3

(7,-3) is the solution

2007-09-15 13:07:00 · answer #3 · answered by Marvin 4 · 0 1

x - y =10
2x + 3y =5

x = y + 10
2 (y+10) + 3y = 5
2y + 20 + 3y = 5
5y = -15
y = -3

x = y + 10
x = -3 +10
x = 7

Hope this helps

2007-09-15 13:09:57 · answer #4 · answered by TENNIS BUM 2 · 0 1

Hold it right there, you messed up on something. -y=10-x, so
y=x-10, then you get 2x +3(x+10)=5. Multiply out and you get 5x=5-30, therefore x=-5. Plug it back in so you get (-5)-y=10
which means that -y=15, so y=15.

2007-09-15 13:05:58 · answer #5 · answered by rotcfreak1 5 · 0 1

y = x - 10
2 x + 3 (x - 10) = 5
2x + 3x - 30 = 5
5x = 35
x = 7

y = 7 - 10
y = - 3

x = 7 , y = - 3

2007-09-16 06:37:13 · answer #6 · answered by Como 7 · 0 1

all of the previous answer are correct, however, i would like point out that the square root of eight can be simplified into 2 root 2... to do this you want to find a perfect square (4,9,16,25 ect.)as a factor of eight 4 and 2 are both factors of eight... so you can break down the square root of eight into the sqaure root of 4 times the square root of 2... as we know the square root of 4 is 2, therefore the simplified form of the square root of eight is 2 root 2

2016-05-20 06:55:26 · answer #7 · answered by Anonymous · 0 0

no the answer is wrong

x-10=y
2x+3(x-10)=5
2x+3x-30=5
5x-30=5
5x=35
x=7


then plug x=7 into x-y=10
so 7-y=10
-y=3
y=-3

hope that helps!!! :)

2007-09-15 14:56:30 · answer #8 · answered by aniketkno 2 · 0 1

That is not correct its 7 just plug in 7 for x in either equation and then solve for y.

2007-09-15 13:03:48 · answer #9 · answered by Bennyboxer 3 · 0 2

x-y = 10
fix to:
-y = 10 - x
y = -10 + x

then replace y with -10 + x
then when you know x, y = -10 + x

2007-09-15 13:04:49 · answer #10 · answered by MrPotatoHead 4 · 0 2

fedest.com, questions and answers